2017
DOI: 10.1080/13880209.2017.1362011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of torilidis fructus ethanol extract through inhibition of Src

Abstract: Context: Torilidis fructus, fruits of Torilis japonica Decadolle (Umbelliferae), is a medicinal herb traditionally used as a pesticide, an astrictive, or a medicine for various inflammatory diseases. Objectives: Due to the lack of pharmacological studies on this herbal medicine, we explored the inhibitory activity of torilidis fructus on the macrophage-mediated inflammatory response using its ethanol extract (Tf-EE). Material and methods: The Griess assay and prostaglandin (PGE2) ELISA assay were conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…SRC also plays vital roles in innate immunity, activation of immune cells, and production of inflammatory cytokines. 26 The activated SRC kinases could promote the inflammatory cells and pro-inflammatory cytokines, and also participate in the inflammatory signaling pathways, including MAPK, 27 NF-κB, 28 and PI3K pathways. 29 MMP9 plays an essential role in the pathogenesis of numerous disorders, especially with inflammatory etiology.…”
Section: Resultsmentioning
confidence: 99%
“…SRC also plays vital roles in innate immunity, activation of immune cells, and production of inflammatory cytokines. 26 The activated SRC kinases could promote the inflammatory cells and pro-inflammatory cytokines, and also participate in the inflammatory signaling pathways, including MAPK, 27 NF-κB, 28 and PI3K pathways. 29 MMP9 plays an essential role in the pathogenesis of numerous disorders, especially with inflammatory etiology.…”
Section: Resultsmentioning
confidence: 99%
“…ese results suggest that Tt-ME selectively inhibited LPS-induced inflammatory signaling in RAW2647 macrophages. Our recent findings reported that Syk and Src contribute to NF-κB-mediated phosphorylation of IκBα at early time points [38,49,50]. Meanwhile, MEK1/2, MKK3/6, TAK1, and IRAK1 are known to be the upstream molecules of ERK, JNK, and p38 [51][52][53].…”
mentioning
confidence: 95%
“…Due to the functional response of Src in inflammatory signaling, inflammation-regulatory activities of Src including cytokine production, migration of macrophages, and inflammatory mediator production have been also found in LPS-treated macrophages [48, 49]. Several compounds or extracts with Src inhibitory property were also proved as anti-inflammatory reagents [14, 5053]. In the AP-1 pathway, Lm-ME suppressed activation of only TAK1 and not IRAK1 and IRAK4 (Figure 3(e)).…”
Section: Discussionmentioning
confidence: 99%